Stasis Before the State Nine Theses on Agonistic Democracy - Vardoulakis, Dimitris (Book collections on Project MUSE., 2018)
How is political change possible when even the most radical revolutions only reproduce sovereign power? Via the analysis of the contradictory meanings of stasis, Vardoulakis argues that the opportunity for political change is located in the agonistic relation between sovereignty and democracy and thus demands a radical rethinking.